A Prospective Observational Study between the Value of Sputum Cytology and FNAC of Bronchial Growth in Diagnosing Lung Cancer at Chattogram Medical College Hospital, Bangladesh - Chowdhury, Mohammad Moinuddin; Arif, Mahmud Hassan; Ekram Ullah, Enshad; Al Mamun, Abdullah; Karim, Mirza Nurul; Biswas, Rajib (Asian Journal of Medical Sciences, 2021)
Background: Lung disease is viewed as perhaps the most far reaching and deadly malignancies all throughout the planet. The most seasoned and most crucial technique is based on sputum cytology. The last outskirts for getting sufficient material are fine needle yearning cytology (FNAC) of bronchial development. Aims and Objective: To relate the meaning of sputum cytology and fine needle goal cytology of bronchial tissue under CT rules for diagnosing cellular breakdown in the lungs. Materials and Methods: This potential observational investigation was completed by the division of medication in Chattogram Medical College Hospital, Chattogram, Bangladesh. Where data was collected from January 2019 to June 2020. A total of 50 patients with a suspected history, symptoms, and risk profile of having primary lung cancer, as demonstrated by chest radiography and CT scan, were chosen for the research population. Fifty patients with clinical and biochemical verification of suspected. All collected data were coding and input in SPSS-25 for further analysis. Both descriptive and inferential statistics were tested. Results: Among the 50 patients the vast majority of the patients were 51-60 years of age and the biggest number of the (94 %) patients were male. Sputum cytology is 8% touchy which isn’t steady with different examinations and CT guided FNAC is 94% sensitive. Conclusion: A definitive point of picture guided histological or cytological examination is to stay away from unnecessary thoracotomy and accomplish a particular determination with sensible exactness and least results. So, in this examination we found that sputum cytology is 8% delicate which isn’t steady with different investigations and CT guided FNAC is 94% touchy to last histological analysis of lung cancer. The discoveries recommended that CT guided FNAC discovered to be protected, feasible and viable.